1995
DOI: 10.1002/pro.5560040822
|View full text |Cite
|
Sign up to set email alerts
|

Molecular model of the N‐terminal receptor‐binding domain of the human CD6 ligand ALCAM

Abstract: CD6-ligand interactions havebeen implicated in the regulation of T-cell adhesion and activation. CD6 is a member of the scavenger receptor family, whereas its human ligand (ALCAM) belongs to the immunoglobulin superfamily. The extracellular region of ALCAM includes five immunoglobulinlike domains. As a fusion protein, the N-terminal extracellular domain of ALCAM (ALCAMDl) binds specifically to CD6. We report the construction, assessment, and analysis of a molecular model of ALCAMDl. The model defines the CDR-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Since previous data indicates that ALCAM is also capable of homophilic interactions, (23,29–31) and ALCAM expression is lost during the in vivo transition from osteoprogenitor to ALP‐positive preosteoblast, (22) we evaluated the possibility that blocking ALCAM‐mediated interactions would influence osteogenic differentiation. Preliminary studies in our laboratory also indicate that undifferentiated MSCs express low levels of CD6 on their surface.…”
Section: Resultsmentioning
confidence: 99%
“…Since previous data indicates that ALCAM is also capable of homophilic interactions, (23,29–31) and ALCAM expression is lost during the in vivo transition from osteoprogenitor to ALP‐positive preosteoblast, (22) we evaluated the possibility that blocking ALCAM‐mediated interactions would influence osteogenic differentiation. Preliminary studies in our laboratory also indicate that undifferentiated MSCs express low levels of CD6 on their surface.…”
Section: Resultsmentioning
confidence: 99%
“…1). To understand better their spatial positions, these residues were mapped on a three-dimensional model of this domain in hALCAM [33] (Fig. 5) .…”
Section: Nonconserved Residues In the N-terminal Domain Of Human And mentioning
confidence: 99%
“…The chicken counterpart of ALCAM is a neural adhesion molecule capable of supporting neurite outgrowth (4,5). Data from the chicken indicate that ALCAM is capable of homophilic interactions (4,5), and the possibility of such interactions has also been suggested on the basis of molecular modeling (7). We have previously reported that COS cells that expressed CD6 were able to bind to ALCAM positive thymic epithelial cells, which suggested that CD6 and ALCAM binding can mediate adhesive interactions between thymocytes and thymic epithelial cells (2).…”
mentioning
confidence: 99%